5S implementation of perception to improve quality culture microenterprises apparel textiles in Northern Cone of Lima - Tinoco Gómez, Oscar (2016)
The research, conducted on a microtextile manufacturing workshop allowed the approach of university life with the reality of micro enterprises in the Northern Cone of Lima. First diagnosis microenterprise is made, both in terms of production process and commercial. A workshop was found whose operations are conducted in a relatively small space, without corresponding data sheets. The implementation of 5S had the active participation of the owner and staff of the micro enterprise, the same that had the most runtime in the first three S (select, seiri, organize, seiton; and clean, seiso). The central finding of the research is positive and significant change in the perceived quality of the staff of the micro enterprise, realizing the importance of the implementation of this tool.